Cultural Conflict vs. Maternal Love in Amy Tan’s The Valley of Amazement - MONICA, J. AMUTHA (International Journal of Psychosocial Rehabilitation, 2020)
The family is an organization of primary relationships graded by highly intricate and diverse kinship. The nature of the mother and daughter relationship plays a determining role in the communal life and psychological well-being of the daughters. The relationship between mothers and daughters are usually seen as involving closer psychic, or emotional identification than other family relationships. This paper addresses the love in mother-daughter relationships and analyzes the links among the generations of mothers and daughters across national boundaries and historical periods as they are manifested in Amy Tan’s The Valley of Amazement (2013).